Economic value of surface water use in Cihideung Sub Watershed, Cisadane Watershed - Fitriani, Dewi; Arief, Harnios; Darusman, Dudung; Hermawan, Rachmad (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Surface water is part of the rainfall flowing above the ground to rivers, lakes, or oceans. One of the surface water resources in West Java is the river water from Cihideung sub watershed. People living in the Cihideung river have traditionally benefited water value as environmental services of the river. They use the water for their livelihood, mainly for agriculture, fisheries, and livestock with their level of income up to Rp.512.250.999,00 per year and expenditure of up to Rp.172.079.999,00 per year. Most of them work as farmers with an average age of 47-53 years and the education level is only elementary school level. They put value of water services about Rp. 237.642.578.707,00 for all house hold in Cihideung Sub Watershed for economic value of water utilization. The quality of water tends to be degrading with existing condition is mild to moderate polluted. The water condition have been decreasing people income and need to be restored among other by upland forest conservation using Payment for Environmental Service schema. The value of water could be managed as a source of fund for the conservation program.